Information Sciences and Systems 2015 30th International Symposium on Computer and Information Sciences (ISCIS 2015) - Abdelrahman, Omer H.; Gelenbe, Erol.; Gorbil, Gokce; Lent, Ricardo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The 30th Anniversary of the ISCIS (International Symposium on Computer and Information Sciences) series of conferences, started by Professor Erol Gelenbe at Bilkent University, Turkey, in 1986, will be held at Imperial College London on September 22-24, 2015. The preceding two ISCIS conferences were held in Krakow, Poland in 2014, and in Paris, France, in 2013.   The Proceedings of ISCIS 2015 published by Springer brings together rigorously reviewed contributions from leading international experts. It explores new areas of research and technological development in computer science, computer engineering, and information technology, and presents new applications in fast changing fields such as information science, computer science and bioinformatics.   The topics covered include (but are not limited to) advances in networking technologies, software defined networks, distributed systems and the cloud, security in the Internet of Things, sensor systems, and machine learning and large data sets.
Advances in Networking Technologies -- Software Defined Networks -- Distributed Systems and the Cloud -- Energy Savings in ICT -- Sensor Systems -- Security in Mobile Networks and the Internet of Things -- Advances in Video And Imaging -- Performance Engineering for Large Scale Systems -- Modeling Methods and their Solutions -- Machine Learning and Large Data Sets.
Keywords: Telecommunication; Computer networks .; Mathematics -- Data processing; Bioinformatics; Communications Engineering, Networks; Computer Communication Networks; Computational Science and Engineering; Computational and Systems Biology